Depression among HIV positive pregnant women in Zimbabwe: a primary health care based cross-sectional study - Eugenia Nyamukoho; Walter Mangezi; Bazondlile Marimbe; Ruth Verhey; Dixon Chibanda (BMC, 2019)
Abstract Background Depression is a common psychiatric disorder that is highly prevalent among people living with HIV (PLWH). Depression is linked to poor adherence to anti-retroviral medication while in the peri-natal period may affect birth outcomes. Intimate partner violence (IPV) has been linked to depression. Little is known about the factors associated with depression in HIV positive pregnant women in Zimbabwe. Methods We carried out a cross-sectional study in 4 busy primary care clinics offering antenatal services during the months of June through to September in 2016. Simple random sampling was used to screen HIV positive pregnant women while they waited to be attended to at each clinic. Eligible women who gave written informed consent were screened using a locally validated screening tool-the Edinburgh Postnatal Depression Scale (EPDS). Results A total of 198(85%) participants were recruited out of 234 that were approached. The mean age of participants was 26.6(SD 4.5), of these, 176 (88.9%) had secondary education or more. A total of 78 (39.4%) (95% CI 32.5-46.3) met criteria for antenatal depression according to the local version of the EPDS. Factors associated with antenatal depression after multivariate analysis were intimate partner violence (IPV) [OR 3.2 (95% CI 1.5-6.7)] and previous history of depression OR 4.1 (95% CI 2.0-8.0)]. Conclusion The prevalence of antenatal depression among HIV positive pregnant women in primary care clinics is high. Factors associated with antenatal depression in pregnant HIV positive women are IPV and previous history of depression. There is need for routine screening for depression during the antenatal period and interventions targeting depression in this population should include components to address IPV.